HUBUNGAN SARANA SANITASI RUMAH DAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS I KEMBARAN KABUPATEN BANYUMAS TAHUN 2018 - diyanti, richani ulfa; Anwar, Choiroel; Gunawan, Asep Tata (Poltekkes Kemenkes Semarang, 2021)
AbstractÂ [The Relationship Between Home Sanitation Facilities And Clean Living Behavior With Diarrhea Case Toward Toddler In The Working Area Of Health Center I Kembaran Banyumas Regency In Year 2018] The number of diarrhea sufferers in the working area of Puskesmas I Kembaran is included in the top 10 most people with disease. Thus, there are 813 diarrhea cases found in 2016. This study aims to determine the relationship between environmental sanitation facilities and clean healthy living behavior (PHBS) with diarrhea cases in the working areaof Puskesmas I KembaranBanyumas regency 2018. Type of research used in this research is analytical with case control approach. There are 66 samples where 22 samples are as case and 44 samples are as control. The variables studied are clean water, disposal facility / latrine, wastewater storage facilities, food and beverage storage, clean water use, disposing of baby's feces and hand washing with soap. Further, the research is analyzed with chi square test, logistic regression, and OR with 95% CI and Î± 0,05. The result of bivariate analysis was obtained by means of environmental sanitation and hygiene and hygienic living behavior which have relation of clean water facilities (p = 0,000, OR = 19,741), disposal facility (P = 0,000; OR = 11,327), food and beverage storage p = 0,000; OR = 14,095), the use of clean water (p = 0,002; OR = 7,800), removing infant stool p = 0,001; OR = 7,286), handwashing with soap (p = 0,006; OR = 6,923). While the waste water disposal facilities have no significant relationship and are not at risk. However, the multivariate analysis shows that the most influential variable is clean water (p = 0,003; RP = 10,663). This research can be concluded that environmental sanitation and clean healthy life behavior can be a risk factor for diarrheal disease. The variable which has the most significant influence is the disposal of feces / latrines. It is recommended that the public always maintain the cleanliness of the environment and apply clean and healthy living behavior.